Religion and State - Development Cooperation: A German-South African Dialogue on Historical and Current Challenges - Koegelenberg, Renier (African Sun Media, 2021)
Intro -- Religion and State: Development Cooperation -- Introduction -- Section I - Challenges posed by global changes and pandemics -- Horst Köhler -- Africa and Europe: a chance for a new start? -- The impact of Covid-19 - and other pandemics -- Mcebisi Jonas -- We need to rethink (just about) everything -- Zwelini Mkhize -- COVID-19: our challenges and partnerships with the religious sector -- Thabo Makgoba -- Resilience and renewal - the role of faith in the response to HIV -- Heinrich Bedford-Strohm -- Church and public theology in times of a pandemic -- Reinhard Marx -- Global Effort in Solidarity - COVID -19 -- Marlene Mahokoto -- Tsantsabane Cares - an emergency food security partnership -- Section II - Religion and state: between cooption and Cooperation -- Church perspectives -- Reinhard Marx -- Holistic Development: Requirements for Development Cooperation in the Age of Globalization -- Thabo Makgoba -- 25 years of democracy in South Africa: the role of churches and religious communities in overcoming apartheid, reconciliation and nation building -- Nelis Janse van Rensburg -- The Dutch Reformed Church (DRC) approach to diaconal work: History is always a long story -- Heinrich Bedford-Strohm -- Religion and State: Between Separation and Cooperation - a German perspective -- Sithembele Sipuka -- Religion and state: between separation and cooperation - a South African perspective -- Political and government perspectives -- Johannes Singhammer -- Religion and state: perspectives for Germany -- Bernhard Felmberg -- Religion and development - opportunities and limitations of cooperation -- Lindiwe Makubalo -- The cooperation between state and church in South Africa's healthcare system -- Hans-Jürgen Papier -- Religion and the state: lessons learned from 70 years' experience of the Federal Republic of Germany.